@maxdancona,
1. Center: (−2, −6);
Solution point: (1, −10)
R^2 = (x -(-2))^2 + (y - (-6))^2
R^2 = (x + 2)^2 + (y + 6)^2
To find R, I must use the distance formula.
Yes?
R = sqrt{(-2 - 1)^2 + (-6 -(-10))^2}
R = sqrt{(-3)^2 + (-6 + 10)^2}
R = sqrt{9 + 16}
R = sqrt{25}
R = 5
If R = 5, then R^2 = 25.
The equation is as follows:
25 = (x + 2)^2 + (y + 6)^2
Is this right?
2. Endpoints of a diameter:
(11, −5), (3, 15).
Let M = midpoint of diameter.
M = [(11 + 3)/2, (-5 + 15)/2]
M = (14/2, 10/2)
M = (7, 5)
I see that the equation is not centered at the origin.
R = sqrt{(7 - 3)^2 + (5 - 15)^2}
R = sqrt{(4)^2 + (-10)^2}
R = sqrt{16 + 100}
R = sqrt{116}
If R = sqrt{116}, then R^2 = 116.
The equation is as follows:
116 = (x - 7)^2 + (y - 5)^2
Is this right?